Discussions that work : task-centred fluency practice - Ur, Penny (New York : Cambridge University Press, 1981)
Contains over fifty exercises designed to encourage fluency practice in the teaching of English as a foreign language.
Includes bibliographical references (p. 119-121) and index.
Adult
Keywords: Discussion; English language -- Spoken English; English language -- Study and teaching -- Foreign speakers; Conversation; English language; English language -- Study and teaching